Berberine-Loaded PVCL-PVA-PEG Self-Assembled Micelles for the Treatment of Liver Fibrosis - Zha X; Hao Y; Ke Y; Wang Y; Zhang Y (International Journal of Nanomedicine, 2024)
Xiaozhu Zha,1,* Yumei Hao,2,* Yifan Ke,1 Yichun Wang,3 Yujia Zhang2 1Department of Traditional Chinese Medicine, Anqing Medical College, Anqing, People’s Republic of China; 2Beijing Key Laboratory of Drug Delivery Technology and Novel Formulation, Institute of Materia Medica, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, 100050, People’s Republic of China; 3Department of Radiation Oncology, the First Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yichun Wang; Yujia Zhang, Email wangechun321@sina.com; zhyj@imm.ac.cnBackground: Liver fibrosis is a necessary pathological process in many chronic liver diseases. Studies have shown that the progression of chronic liver disease can be slowed by rational intervention in hepatic fibrosis. Berberine (BBR), a natural extract of Phellodendron amurense, inhibits the development of liver fibrosis through several mechanisms. However, the clinical application of BBR is limited due to its low solubility. Drug delivery systems have been developed to improve the solubility of hydrophobic drugs and increase their efficacy in treating the liver fibrosis.Methods: In this study, a biocompatible nanomicelle was constructed by thin-film dispersion method using polyvinyl caprolactam-polyvinyl acetate-polyethylene glycol graft copolymer (PVCL-PVA-PEG) as a carrier to encapsulate BBR (PVCL-PVA-PEG/BBR-MCs) to improve the solubility of BBR and reduce the systemic side effects. The ability to inhibit HSC-T6 cell activation of PVCL-PVA-PEG/BBR-MCs was evaluated in vitro. The anti-hepatic fibrosis effects of PVCL-PVA-PEG/BBR-MCs were investigated in vivo.Results: PVCL-PVA-PEG/BBR-MCs have a uniform spherical shape with a mean particle size of 60.04 ± 0.027 nm and a potential of 1.49 ± 0.32 mV. It had an encapsulation efficiency of 98.52% ± 0.70 and drug loading content of 6.16% ± 0.04. Compared to free BBR, PVCL-PVA-PEG/BBR-MCs significantly inhibited HSC-T6 cell activation and TGF-β 1-induced HSC-T6 cell migration in vitro. In vivo biodistribution experiments showed significantly improved hepatic distribution of PVCL-PVA-PEG/DiD-MCs compared to free DiD, suggesting that PVCL-PVA-PEG micelles enhance the ability of BBR to enter the liver and improve therapeutic efficacy. After treatment, PVCL-PVA-PEG/BBR-MCs significantly improved fibrotic liver structure and reduced collagen deposition in comparison to the CCl4-treated group; the treatment outcome was more effective than that of the free BBR group.Conclusion: Our results demonstrate the advantages of encapsulating BBR in PVCL-PVA-PEG micelles and highlight the potential of PVCL-PVA-PEG/BBR-MCs as a therapeutic strategy for the treatment of liver fibrosis. Keywords: liver fibrosis, berberine, hepatic stellate cells, PVCL-PVA-PEG, drug delivery system